Analisis Efektivitas Dan Kontribusi Potensi Penerimaan Pajak Daerah Terhadap Pendapatan Asli Daerah (PAD) - Dini Andriyani; Ridha Azka Raga; Imam Purwanto (AKUNTANSI 45, 2023)
Tax is a contribution that must be paid by Indonesian citizens when carrying out transactions. Taxes are paid by the people and for the people as a source of government revenue. Restaurant Tax, Hotel Tax, Entertainment Tax, Street Lighting Tax and Advertisement Tax are potential regional revenues that must be managed optimally. This research aims to determine and analyze the effectiveness of revenue from Restaurant Tax, Hotel Tax, Entertainment Tax, Street Lighting Tax and Advertisement Tax along with their contribution to Original Regional Income in Tangerang City for the 2019-2021 period. The type of data used in this research is quantitative data which refers to information collected from existing sources. The analysis technique in this research uses descriptive analysis methods with quantitative analysis tools in the form of effectiveness and contribution calculation formulas.